Population problems of Sri Lanka : proceedings of a seminar. - University of Sri Lanka, Colombo Campus. Demographic Training & Research Unit.; Seminar on the Population Problems of Sri Lanka in the Seventies (1975 : Colombo, Sri Lanka) (Colombo: Demographic Training and Research Unit, University of Sri Lanka, Colombo Campus, 1976)
Proceedings of the Seminar on the Population Problems of Sri Lanka in the Seventies, 1975, Colombo, organized by the Demographic Training & Research Unit, University of Sri Lanka, Colombo Campus.
Includes statistical tables.
Includes bibliographies.
Keywords: Fertility, Human -- Sri Lanka -- Congresses; Family policy -- Sri Lanka -- Congresses; Sri Lanka -- Population policy -- Congresses